Monkey girl: evolution, education, religion, and the battle for America's soul - Humes, Edward (Ecco, 2007)
What should we teach our children about where we come from? Is evolution good science? Is it a lie? Is it incompatible with faith? Did Charles Darwin really say man came from monkeys? Have scientists really detected "intelligent design"--evidence of a creator--in nature? Inside our DNA? Inside amazing molecular "machines" within our very cells? Or are those concepts nothing more than scientific fool's gold, tricks designed to sneak religious ideas into public school classrooms? What happens when a town school board decides to confront such questions head-on, thrusting its students, then an entire community, onto the front lines of America's culture wars? This book takes you behind the scenes of the recent war on evolution in Dover, Pennsylvania, the epic court case on teaching "intelligent design" it spawned, and the national struggle over what Americans believe about human origins--told from the perspectives of all sides of the battle.--From publisher description